ANALISIS KEMAMPUAN PEMAHAMAN KONSEP SISWA SMP PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Diaz, Maria Esterlita; Marlina, Rina (Universitas Bhinneka PGRI, 2024)
This research was conducted with the aim of observing and describing junior high school students' ability to understand concepts in two-variable linear equation systems. 36 students of class VIII SMP Negeri 3 West Karawang were the research subjects. This research uses a qualitative descriptive approach, and the data collected for this research comes from tests that measure students’s ability to understand concepts. The results showed that students in the low category, with 7 students, had a concept understanding ability of 19.4%. The medium category with 23 students, has a concept understanding ability of 63.9%. Meanwhile, in the high category with 6 students, students’ concept understanding ability was 16.7%. It can be said that the majority of students at SMP Negeri 3 West Karawang haave the ability to understand mathematical concepts in the medium category.